Description of Fenerbahce devosi (Cyprinodontiformes: Nothobranchiidae), a new species of dwarf killifish from the eastern Congo Basin in the Democratic Republic of Congo - Sonnenberg, Rainer; Woeltjes, Tonnie; der Zee, Jouke R. Van (Zootaxa, 2011)
A new species of the currently monotypic genus Fenerbahce is described from the eastern Congo Basin. It is distinguished from F. formosus from the western Congo Basin by several characters, of which the most prominent are: a more anterior origin of dorsal fin relative to anal fin, a deeper body, long extension on edges of the caudal fin, and a distinct colour pattern. The distinctness of the two species is supported by additional morphological characters and the results of a preliminary analysis of mitochondrial and nuclear DNA sequences.